Prevalence, Risk Factors, and Genotypes of Toxoplasma gondii in Food Animals and Humans (2000–2017) From China - Dong, Hui; Su, Ruijing; Lu, Yaoyao; Wang, Mengyao; Liu, Jing; Jian, Fuchun; Yang, Yurong (Frontiers in Microbiology, 2018)
Toxoplasma gondii as a food-borne pathogen, the infection of it in food animals has relation with human toxoplasmosis, but the trends and epidemiological features of T. gondii infections in food animals are rarely studied in China. The aimed of this study was to assess the epidemiology and risks of T. gondii in sheep, goats, swines, chickens, yaks, cattle and humans from 2000 to 2017 and to explore prevention and control strategies. The overall seroprevalence of T. gondii infections in food animals is 23.7% (39,194/165,417, 95%CI, 23.49%-23.90%), which is significantly higher than that in humans (8.2%, 95%CI, 8.06%-8.39%, 8,502/103,383) (P<0.0001). Compared the prevalence of T. gondii infections in animals and humans sampled from 2000-2010, it was significantly increased in the period 2011 to 2017 (P<0.0001). Compared the food animals from non-Yangtze River, animals from regions of the Yangtze River have high seroprevalence rates for T. gondii (P<0.0001). Furthermore, samples from the western to eastern regions of the Yellow River showed an increase in seroprevalence for T. gondii (P<0.0001). It was speculated that T. gondii oocysts may be transmitted by water, effective prevention and control strategies are including water filtration or water boiling, inactiving oocysts from feline’s feces, monitoring birds and rodents. Chinese 1 (ToxoDB#9) is the predominant genotype in food animals from China.